Human factors in occupational health and safety 4.0: a cross-sectional correlation study of workload, stress and outcomes of an industrial emergency response. (17th May 2019) - Nicoletti, Letizia; Padovano, Antonio
Industrial hazards and emergency response capability assessment studies are still poorly focusing on the impact of human factors on the response phase in the aftermath of an industrial accident. This study pushes for an increased attention on human factors, such as stress and perceived workload, in the occupational health and safety 4.0 and proposes an approach to analyse their effects with the ultimate aim to include them in the design of industrial safety protocols and regulations and in the assessment of hazards. The present paper answers the question whether and to what extent stress and the perceived workload are correlated to the capability of the emergency manager to coordinate and monitor the execution of all the actions intended to deal with an industrial accident and its effects. The findings of a cross-sectional regression of data collected from a series of training sessions carried out by means of virtual reality and serious games technologies show how a balanced workload and the ability to control emotivity are preconditions for mastering procedures and responding in the optimal way to an industrial emergency scenario.